Synergetic effects of doxycycline-loaded chitosan nanoparticles for improving drug delivery and efficacy - Cover NF (Dove Medical Press, 2012)
Natasha F Cover1, Susana Lai-Yuen2, Anna Parsons3, Arun Kumar41Department of Chemical and Biomedical Engineering, University of South Florida, Tampa, Florida, 2Department of Industrial and Management Systems Engineering, University of South Florida, Tampa, Florida, 3Department of Obstetrics and Gynecology, University of South Florida, Tampa, Florida, 4Department of Medical Technology, University of Delaware, Newark, Delaware, USAIntroduction: Doxycycline, a broad-spectrum antibiotic, is the most commonly prescribed antibiotic worldwide for treating infectious diseases. It may be delivered orally or intravenously but can lead to gastrointestinal irritation and local inflammation. For treatment of uterine infections, transcervical administration of doxycycline encapsulated in nanoparticles made of biodegradable chitosan may improve sustained delivery of the drug, thereby minimizing adverse effects and improving drug efficacy.Methods and materials: As a first step toward assessing this potential, we used an ionic gelation method to synthesize blank and doxycycline-loaded chitosan nanoparticles (DCNPs), which we then characterized in terms of several properties relevant to clinical efficacy: particle size, shape, encapsulation efficiency, antibacterial activity, and in vitro cytotoxicity. Two particle formulations were examined, with one (named DCNP6) containing approximately 1.5 times the crosslinker concentration of the other (DCNP4).Results: The two formulations produced spherically shaped drug-loaded nanoparticles. The spheres ranged in size from 30 to 220 nm diameter for DCNP4 and 200 to 320 nm diameter for DCNP6. Average encapsulation yield was 53% for DCNP4 and 56% for DCNP6. In terms of drug release, both formulations showed a burst effect within the first 4 to 5 hours, followed by a slow, sustained release for the remainder of the 24-hour monitoring period. The in vitro antibacterial activity against Escherichia coli was high, with both formulations achieving more than 90% inhibition of 4-hour bacterial growth. Cytotoxic effects of the DCNPs on normal human ovarian surface epithelial cells were significantly lower than those of unencapsulated doxycycline. After 5 days, cultures exposed to the unencapsulated antibiotic showed a 61% decrease in cell viability, while cultures exposed to the DCNPs exhibited less than a 10% decrease.Conclusion: These laboratory results suggest that DCNPs show preliminary promise for possible eventual use in transcervical drug delivery and improved efficacy in the treatment of bacterial uterine infections.Keywords: chitosan, doxycycline, ionic gelation, nanoparticles, cytotoxicity